PERSEPSI WARGA BINAAN TERHADAP PEMBINAAN MENTAL DI LEMBAGA PEMASYARAKATAN - Fatmawati Fatma; Nasrah Natsir Nasrah (JAPPA: Jurnal Andragogi Pedagogi dan Pemberdayaan Masyarakat, 2022)
Efforts to mentally foster citizens in community institutions based on the correctional system are no longer seen as an effort to foster punishment, but are intended as the most appropriate step in providing education and guidance to them. This research uses a qualitative approach with a type of case study research. The implementation of the program of coaching and handling assisted citizens at the Klas II A Sungguminasa Narcotics Correctional Institution is given so that they have more productive activities, even though they have violated the law that makes them have to deal with the law. By participating in a mental coaching program, they can change for the better and are optimistic about their future to make various positive and productive efforts. The mental coaching program is said to be productive because the results can be used as a source of livelihood in meeting the needs of life for themselves and their families